The Financial Crisis in Ecuador, 1998-2000 - García Osorio, Nelson (2013)
This study is an analysis of the problems of the financial system that led Ecuador to face a socioeconomic crisis, the fragility of the Ecuadorian financial system was evident in the salvage of Filanbanco in November 1998, which had repercussions on the exchange rate, deprecation of the sucre and capital flight, aggravating the liquidity of the financial system, which resulted in the closure of some banks, incling Progreso Bank, considered the second Bank in the country by size of assets and one of the most profitable institutions. Subsequently, in March 1999, a "banking holiday" happened, that froze bank deposits, affecting the financial and economic activity of the country and deepened the problem of insolvency in the financial system, resulting in dollarization of the country in January 2000, as a means of departure for monetary stabilization.